2016
DOI: 10.1186/s12872-016-0226-2
|View full text |Cite
|
Sign up to set email alerts
|

Relationship and prognostic importance of thyroid hormone and N-terminal pro-B-Type natriuretic peptide for patients after acute coronary syndromes: a longitudinal observational study

Abstract: BackgroundAltered thyroid function and increased rates of N-terminal pro-B-Type natriuretic peptide (NT-pro-BNP) are highly prevalent in coronary artery disease (CAD) patients with heart failure, and are associated with unfavorable prognosis. This study was undertaken to examine the relationship and prognostic impact of thyroid hormones, inflammatory biomarkers, and NT-pro-BNP on long-term outcomes in patients after acute coronary syndrome (ACS).MethodsThe study comprised of 642 patients (age 58 ± 10 years, 77… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 54 publications
(66 reference statements)
3
44
0
2
Order By: Relevance
“…The increased rate of in-hospital CV death in post-AMI patients with LT3S found in our study is consistent with previous reports [1,16,22]. ROC showed AUC of 0.741 with lower levels of fT3 for inhospital CV death.…”
Section: Discussionsupporting
confidence: 92%
“…The increased rate of in-hospital CV death in post-AMI patients with LT3S found in our study is consistent with previous reports [1,16,22]. ROC showed AUC of 0.741 with lower levels of fT3 for inhospital CV death.…”
Section: Discussionsupporting
confidence: 92%
“…A decrease in serum T3 has been found to be a predictor of larger myocardial injury size [ 4 , 5 , 7 ], worse cardiac function [ 8 , 9 ], greater thrombus burden [ 10 ], and a poorer prognosis [ 5 , 11 14 ] in AMI. A recent study also confirmed the association between free T4 and adverse outcomes in acute coronary syndrome [ 15 ]. Serum T3, which is the most important bioactive thyroid hormone for cardiomyocytes, is mostly produced by the peripheral process of deiodination of T4 [ 6 ].…”
Section: Introductionmentioning
confidence: 55%
“…Two further larger studies involving consecutive STEMI patients undergoing primary percutaneous coronary intervention also have related the low T3 syndrome to increased short‐ and long‐term mortality . Moreover, a recent study with patients attending a cardiac rehabilitation program after an ACS also has reported an association of lower fT3 levels with all‐cause mortality …”
Section: Prognostic Value Of Thyroid Hormones In Acsmentioning
confidence: 94%
“…30,31 Moreover, a recent study with patients attending a cardiac rehabilitation program after an ACS also has reported an association of lower fT3 levels with allcause mortality. 38 Alterations in THs are more evident in critically ill patients. Not surprisingly, a study comparing the thyroid function of patients with resuscitated cardiac arrest due to ACS and patients with uncomplicated AMI showed that the latter group was characterized by a milder form of the low T3 syndrome.…”
Section: Effects Of Thyroid Hormones On the Cardiovascular Systemmentioning
confidence: 99%